Ownership Concentration and Market Power in Urban Land Markets - Markusen, J. R.; Scheffman, D. T. (Review of Economic Studies, 1978)
James R. Markusen, David T. Scheffman; Ownership Concentration and Market Power in Urban Land Markets, The Review of Economic Studies, Volume 45, Issue 3, 1 Oct